INNOVATION IN EDUCATION AS A NECESSI - Шуст, Наталія Борисівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: the purpose of this article is an attempt to study how innovations in education transformational society become the need of targeted development and recognition in the world community. The higher education is not аn unchanging institution and all the time responding to the new civilization challenges and social realities. However, the updating of the educational process and scientific research takes place is not always consistent, and sometimes hastily and contradictory. Methods of research: the methodological basis of the research was formed by general scientific methods of cognition. Results: the original principle of the proposed scientific research is the development of theoretical systems and designs shaping the need for innovation in educational sphere taking into account Ukrainian reality. In terms of the change of social development innovation in education are becoming more necessary and are continuous in nature. Discussion: modern processes in the society contribute not only rethinking features development education, science and also actualize needs the implementation of innovation in the sphere. Innovations are essential to the formation of the principles of development and stability, sustainable progress and a mechanism for the progressive development of both education and Ukrainian society as a whole.